Experience of Generation Z Nursing Professional Do Not Like the Department of Worked - Wongsaree, Chutchavarn; Phunthong, Supaluk; Jantiya, Sudthicharat (Journal of The Royal Thai Army Nurses, 2020)
This descriptive qualitative research aimed to describe experience of generation Z nursing professional do not like the department of worked using Edmund Husserl phenomenology approach. Key informants were 26 generation Z nursing professional do not like the department of worked. Recruited by purposing sampling and snowball method from a public hospitals and private hospitals in Bangkok, Thailand. Data were collected through in-depth interviews, observations, and tape record. Clolaizzi approach and Atlas ti 6.1 program for content analysis was used to analyze data in this study. Research results: Experience of generation Z nursing professional do not like the department of worked could be categorized into 5 major themes: 1) Even though do not like the department of worked must do it first because there is no right to choose, that is, the informant accepts funding to work after graduation therefore had to work in the department that the hospital provided. 2) Patiently work in a department that doesn’t like it first, hoping to move to work in the department that you like. 3) Even though it is a department that he does not choose, he is willing to continue working because he sees the opportunity to advance in his duties. 4) Friends are influential to the ideas and decisions of generation Z nurses in choosing work after graduation. and 5) The misunderstandings of people in the department are the factors that cause generation Z nurses to resign faster.